Spatial Mapping of Healthcare-Associated Infections (HAIs) Risks Based on Sanitation Facility Availability and Patient Density Ratios in Hospitals Across Indonesia - Sari, Mila (Journal of Health Service Administration and Hospital Management, 2026)
Patient safety regarding the persistent threat of Healthcare-Associated Infections (HAIs) remains a critical challenge in Indonesia, driven by significant infrastructural disparities and operational strains. This study aims to map the national geospatial risk of HAIs by testing the hypothesis that the intersection between sanitation limitations and patient density creates distinct regional risk clusters. Adopting a quantitative descriptive design with retrospective spatial analysis, the research examines secondary data from 3,155 hospitals across 38 provinces, sourced from Siranap, RS Online, and the Indonesian Health Profile for the 2022-2024 period. Key variables, including handwashing station availability, potable water access, and Bed Occupancy Rate (BOR), were integrated using Spatial Join techniques. The results reveal a "Dual-Risk Landscape": metropolitan regions in Java-Bali exhibit elevated risks due to BOR saturation (>82%), while Eastern Indonesia faces high vulnerability from basic infrastructure deficits (water access <68%) despite lower patient density. Statistical analysis confirms that the synergy between sanitation compliance and BOR accounts for 46% of the national infection risk variance ( ). These findings imply a necessary shift from generalized policies toward region-specific interventions prioritizing facility engineering. In conclusion, this mapping proves that urban density management and peripheral infrastructure investment are pivotal for HAIs mitigation. It is recommended that health authorities integrate real-time environmental sensor-based early warning systems for future risk monitoring.